Molecular Docking of Natural Compounds from Tulsi (Ocimum sanctum) and neem (Azadirachta indica) against SARS-CoV-2 Protein Targets - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Background: Antiviral activity of tulsi and neem extracts are widely reported. Selected natural compounds from tulsi and neem were hence screened for their efficacy against SARS-CoV-2 targets. Materials and Methods: Using molecular docking tools, the binding efficacy ofnatural compounds from tulsi and neem were tested against three key SARS-CoV-2 targets i.e., 1) surface glycoprotein (6VSB) responsible for viral attachment, 2) RNA dependent RNA polymerase (6M71) responsible for viral replication and 3) main protease (6Y84) responsible for viral replication. Results: Methyl eugenol, oleanolic acid and ursolic acid had high binding efficacy against surface spike glycoprotein and RNA polymerase of SARS-CoV-2. Epoxyaza- diradione, Gedunin, Methyl eugenol, Oleanolic acid and Ursolic acid showed high binding efficacy against the main protease of SARS-CoV-2. Binding efficacy of natural compounds from tulsi and neem was superior to that of the standard drugs Lopinavir/Ritonavir and Remdesivir. Conclusion: Natural compounds from tulsi and neem have high binding efficacy against SARS-CoV-2 targets involved in viral attachment and replication, hence will be useful in the management of infection caused by SARS-CoV-2.
Keywords: Protease inhibitors; RNA polymerase inhibitors; Coronavirus; Covid-19; Antiviral drugs; SARS-CoV-2; Viral entry; Glycoprotein